SUSTAINABLE LIVELIHOOD ANALYSIS THROUGH CORPORATE SOCIAL RESPONSIBILITY PROGRAM (case study on the Sima and Wami communities in Nabire Papua) - Iyai, Yosinta; Mulkhan, Unang; Saptiani, Fenny (Jurnal Kompetitif Bisnis, 2023)
Corporate Social Responsibility (CSR) is a company's pledge to take part in sustainable economic development in order to raise community standards of living and create a win-win situation for the business, the local community, and society at large. CSR is known as a dharma in Indonesia. The most crucial factor for businesses operating in the natural resource sector is stated in Article 74 of the Limited Liability Company Law number 40 of 2007. PT Nabire Baru only dredged the natural wealth of two villages in the Yaur district of Nabire Regency, which led to peeling, highways and bumps, caused by large vehicles and large equipment that damaged access to the two asphalt villages left alone, while those were repaired but took a long time. In reality, oil palm companies are still thought to be lacking in providing programs that support CSR. just enough Therefore, the purpose of this study is to ascertain the application and implementation of corporate social responsibility in accordance with Article 74 of the Limited Liability Company Law No. 40 of 2007 in one of the oil palm companies, PT Nabire Baru.